Legal Protection of Children as Witnesses in the Crime of Rape - Erna Dewi; Volanda Azis Saleh (Faculty of Law, Universitas Lampung, 2020)
Legal protection for victim witnesses in the trial becomes an important issue that must be addressed. because in the field implementation there were not a few victims witnesses worried about giving their testimony at the trial because there was no legal certainty in the form of protection in the trial. The problem in writing this thesis is how is the legal protection of children as witnesses in cases of rape crimes? Why are there obstacles to the protection of children as witnesses in cases of rape crimes? This study uses a juridical normative and empirical approach. Normative research is done on things that are theoretical principles of law, while the empirical approach is done to study the law in fact in the field. Based on the results of the study, the legal protection of children who are witnesses in criminal cases against children who are victims in court cases can give their testimony without having tobe present when examining their cases in court, by using means related to video call or helping to uncover question that arises read out in court and Factors occur obstacles to the protection of children as witnesses in cases of first rape crimes, Factors of Witness and Victim Protection Agency that do not have representatives in the area and lack of socialization, Second Unregulated Form of Witness Protection in the Criminal Procedure Code so that witness protection does not get legal certainty. Third, the Cooperation between Witness and Victim Protection Institutions has not been effective with Law Enforcement Agencies. The suggestions that can be conveyed in this study should law enforcement should provide optimal protection to victims' witnesses until the threat and intimidation is completed on the victim. The government should immediately renew the Child Protection .Act and the Victim witness Protection Act concerning the form of protection for child witnesses as a victim who can provide his statement using telecommunications facilities in the form of video calls or acknowledge written witness statements and then read out in court.